Implementasi Model Pembelajaran Sorogan-Bandongan pada Materi Asam Basa untuk Meningkatkan Pemahaman Konsep Peserta Didik - Nur Khofifah; Rinaningsih (PendIPA Journal of Science Education, 2026)
This study examines the implementation of the Sorogan-Bandongan learning model, which integrates individual learning with traditional teaching methods in the context of acid-base subject matter. This research was conducted to examine and measure the extent to which students' conceptual understanding improved following the implementation of this learning model. This study employs a pre-experimental method with a One Group Pretest-Posttest design, involving 36 eleventh-grade students of SMA Negeri 1 Menganti as research subjects. Research data were collected through instruments in the form of test sheets consisting of a pretest and posttest. The Sorogan-Bandongan learning stages applied included: independently reading material and completing tasks on a handout (Sorogan), administering a diagnostic test, teacher-led delivery of subject matter, completing Student Worksheets in groups (Bandongan), class discussion for content reinforcement (Bandongan), and administering a final test. The research findings indicate a fairly significant improvement in students' conceptual understanding, as reflected in the rise of the average pretest score from 52.57 to 88.09 on the posttest. This achievement is further supported by an N-Gain score of 0.75, which falls within the high category, indicating that the implementation of the Sorogan-Bandongan learning model was successful and effective in promoting the improvement of students' conceptual understanding, making it a potential alternative teaching approach in chemistry education.